Jaringan Ulama: Pembaharuan dan Rekonsiliasi dalam Tradisi Intelektual Islam di Dunia Melayu-Indonesia - Oman Fathurahman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
Book Review: Azyumardi Azra, The Origins of Islamic Reformism in Southeast Asia: Networks of Malay-Indonesian and Middle Eastern 'Ulama' in the Seventeenth and Eighteenth Centuries, Australia: Allen & Unwin, 2004, ix + 254 pagesThis book attentpts to enrich and -in a number of important ways- also to revise this nomenclature of